2017
DOI: 10.5194/nhess-17-467-2017
|View full text |Cite
|
Sign up to set email alerts
|

Landslides, floods and sinkholes in a karst environment: the 1–6 September 2014 Gargano event, southern Italy

Abstract: Abstract. In karst environments, heavy rainfall is known to cause multiple geohydrological hazards, including inundations, flash floods, landslides and sinkholes. We studied a period of intense rainfall from 1 to 6 September 2014 in the Gargano Promontory, a karst area in Puglia, southern Italy. In the period, a sequence of torrential rainfall events caused severe damage and claimed two fatalities. The amount and accuracy of the geographical and temporal information varied for the different hazards. The tempor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In particular, from 1 to 6 September 2014, the study area was affected by a strong meteorological event that caused floods and heavy damage throughout the whole Gargano [19]. The most affected zones were those of recent development in the depressed areas of the basin.…”
Section: The Study Areamentioning
confidence: 99%
“…In particular, from 1 to 6 September 2014, the study area was affected by a strong meteorological event that caused floods and heavy damage throughout the whole Gargano [19]. The most affected zones were those of recent development in the depressed areas of the basin.…”
Section: The Study Areamentioning
confidence: 99%
“…Both types of sinkholes have similar mechanisms, and the detailed process of occurrence is as follows (Brinkmann et al, 2008;Caramanna et al, 2008;Kuwano et al, 2010a;Martinotti et al, 2017;Oosthuizen and Richardson, 2011;Rogers, 1986): (1) A cavity is formed underground by external factors (the watersoluble ground layer dissolves in groundwater to cause a natural sinkhole, or soil erosion occurs along with the groundwater outflow due to sewage damage or excavation to cause an anthropogenic sinkhole). 2The groundwater level rises during rainfall and falls after the rainfall, causing the soil around the cavity to be lost and the cavity to expand.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a growing need to study the correlation between rainfall intensity and sinkhole occurrence. Martinotti et al (2017) showed that a period of torrential rain and the rainfall intensity triggered the natural sinkholes in Italy. Gao et al (2013) confirmed that the groundwater level rise due to extremely heavy rainfall has a significant effect on sinkhole generation in a karst environment in China.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the understanding of the vulnerability of karst environment has reached a new height, which greatly facilitated the settlement of the degradation and pollution problems [5,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%